Systems auditability and control report (Institute of Internal Auditors Research Foundation Altamonte SpringsUS, 1991)
Provides guidance on the control and audit of information systems and technology. Focuses on the business perspective of information technology and the risks associated with planning, implementing and using automation.
Contents: Module 1 : Executive summary. - Module 4 : Managing computer resources. - Module 9 : Security. - Module 10 : Contingency planning